Fans, blockbusterisation, and the transformation of cinematic desire : global receptions of the Hobbit film trilogy - Michelle, Carolyn; Davis, Charles H.; Hardy, Ann L.; Hight, Craig (London : Springer Nature, 2017)
This book explores the evolution of audience receptions of Peter Jacksons Hobbit trilogy (2012-14) as an exemplar of the contemporary blockbuster event film franchise. Drawing on findings from a unique cross-cultural and longitudinal study, the authors argue that processes and imperatives associated with Hollywood blockbusterisation shaped the trilogys conditions of production, format, content, and visual aesthetic in ways that left many viewers progressively disenchanted. The chapters address public and private prefigurations of the Hobbit trilogy, modes of reception, new cinematic technologies and the Hobbit hyperreality paradox, gender representations, adaptation and the transformation of cinematic desire, and the role of social and cultural location in shaping audience engagement and response. This book will appeal to audience researchers, Q methodologists, scholars and students in film and media studies, Tolkien scholars, and Hobbit fans and critics alike.
1. Returning to Middle-earth, in Blockbusterised Form -- 2.Researching Audience Engagements with the Hobbit Trilogy: A Unique Methodological Approach -- 3.Adaptation, Anticipation, and Cinematic Desire: Prefigurative Engagements with a Blockbuster Fantasy Franchise -- 4.Unexpected Controversies Cast a Shadow over Middle-earth -- 5.The Saga Begins: Mapping Audience Reactions to An Unexpected Journey -- 6.The Rise of the Hobbit Critic: From The Desolation of Smaug To The Battle of the Five Armies -- 7.Pioneering Cinematic Technologies and the Hobbits Hyperreality Paradox -- 8.On the Transformation of Meaning and Cinematic Desire -- 9.Making Sense of Difference: How Social Location and Identity Shaped Engagements with the Hobbit Trilogy -- 10.Conclusion and Methodological Reflections on a Unique Project.
Keywords: Culture -- Study and teaching; Motion pictures; Cultural and Media Studies; Film Theory; Cultural Theory; Global Cinema; mediatutkimus; kulttuurintutkimus; elokuvataide; elokuvat; reseptio; elokuvat (teokset); vastaanotto (reseptio)